Integrated System-on-Module for Design-Space Exploration of Spiking Neural Networks - El-Masry, Moamen; Kourany, Taher; Kho, Rex; Werner, Thilo; Zjajo, Amir; Weigel, Robert (AICAS 2023 - IEEE International Conference on Artificial Intelligence Circuits and Systems, Proceeding, 2023)
We present an integrated system-on-module for design-space exploration of neurosynaptic behavior of complex, non-volatile memory enhanced, spiking neural networks. The system operates in a locally-analog, globally-digital manner, which enables both exploration and validation of individual computational components and characteristic spike-based features of neurosynaptic arrays. The system components are reconfigurable, adaptable and interchangeable enabling reproducible, precise firing patterns. The platform is coupled with an embedded resistive-RAM which acts as a weight retention mechanism. Experimental results obtained in 28 nm CMOS technology illustrate the feasibility of the methodology.
CRIS-Team Scopus Importer:2023-08-11
Keywords: near-memory computing; neuromorphic; non-volatile memory; resistive-RAM; Spiking neural networks; system-on-module